Aspects of sustainable rural development in the mountain areas from n-e region of Romania - Silviu, Beciu; Nistor, Stefania; Popa Oana, Ecaterina; Alecu, Iulian (Economics of Agriculture, 2010)
This paper intend to develop a methodology regarding actual size evaluation and the perspective of sustainable rural development through the elaboration of swot analysis, as method of strategic planning for the mountanian areas from the North-East Region of Romania.